2020
DOI: 10.1192/bjo.2020.58
|View full text |Cite
|
Sign up to set email alerts
|

Double stigma in mental health: epilepsy and mental illness

Abstract: Background Epilepsy and mental illness share similar problems in terms of stigma, as a result of centuries of superstition, ignorance and misbeliefs. Stigma leads not only to discrimination and civil and human rights violations but also to poor access to healthcare and non-adherence or decreased adherence to treatment, ultimately increasing morbidity and mortality. Despite continuous efforts in fighting stigma in these conditions, there is very limited knowledge on the phenomenon of double stigma, meaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Although three quarters of our cohort claimed to be in good health, about 60% stated that they had experienced symptoms of depression. It should be noted that patients suffering from both epilepsy and a psychiatric condition may be subjected to double stigmatization 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although three quarters of our cohort claimed to be in good health, about 60% stated that they had experienced symptoms of depression. It should be noted that patients suffering from both epilepsy and a psychiatric condition may be subjected to double stigmatization 18 …”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that patients suffering from both epilepsy and a psychiatric condition may be subjected to double stigmatization. 18 Some older studies have revealed that stigma is positively associated with impaired self-esteem, self-efficacy, sense of mastery, perceived helplessness, increased somatic symptomatology, increased rates of anxiety and depression, and reduced life satisfaction. [19][20][21] Baker et al 22 undertook a systematic review on this topic in North and South America, Europe, and Australia and found, from the 33 papers from 25 studies, that being married was associated with lower levels of experienced stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy is still a highly stigmatized condition, leading to discrimination and marginalization. 11 The social limitations (eg, loss of driving privileges), the unpredictable nature of seizures, and the potential social embarrassment associated with them can lead to poor self-esteem, social withdrawal, isolation, and distress. At the same time, several biological factors contribute to the increased occurrence of psychiatric disorders.…”
Section: Psychiatric Disorders In Epilepsymentioning
confidence: 99%
“…'Double stigma' is the impact of having two co-occurring stigmatized conditions within the same individual, such as epilepsy and mental illness. Ultimately this can result in reduced ability to access healthcare, discrimination, decreased adherence to treatment, poor health outcomes, and poor quality of life [7]. Increasingly, improving the mental health and quality of life of PWE is recognized as a treatment goal in its own right [8].…”
Section: Introductionmentioning
confidence: 99%